Implementation of Material Requirements Planning to Minimize Stockout and Material Procurement Costs in Volume Damper Production - Adiksa Madha Putra; Siti Mundari (JRSI (Jurnal Rekayasa Sistem dan Industri), 2026)
Surplus materials generated from textile production processes often remain underutilized due to the lack of integration between manufacturing and retail operations, resulting in idle inventory, unrecorded transactions, and lost sales opportunities. This study aims to improve sales performance and inventory utilization in textile SMEs through the implementation of Odoo ERP with intercompany and e-commerce integration. The study was conducted in a textile SME consisting of a production unit and a retail unit operating under separate business entities. The System Development Life Cycle (SDLC) using the waterfall model was employed to analyze requirements, design the system, configure Odoo modules, and perform functional testing and user acceptance evaluation. The proposed solution enables the automatic generation of intercompany transactions, including Sales Orders, Purchase Orders, and Vendor Bills, while synchronizing inventory, sales, and accounting information in real time. In addition, the e-commerce module provides a digital sales channel for surplus materials that were previously marketed through conventional methods. The results indicate that the integrated system improves transaction traceability, reduces manual data entry, and enhances inventory visibility across business units. Furthermore, the utilization rate of surplus materials increased from 17% prior to implementation to full absorption through the integrated digital channel during the evaluation period, eliminating idle inventory and creating additional economic value. These findings demonstrate that ERP-enabled intercompany integration can support operational efficiency and strengthen sales performance in textile SMEs